Outsourcing cost and tax progression under Nash wage bargaining with flexible outsourcing - Erkki Koskela (Center for Economic Studies and ifo Institute (CESifo), 2010)
It is analyzed the impacts of outsourcing cost and wage tax progression under labor market imperfections with Nash wage bargaining and flexible outsourcing. With sufficiently strong (weak) labor market imperfection, lower outsourcing cost has a wage-moderating (wage-increasing) effect so that there is a negative (positive) effect on equilibrium unemployment. Higher tax progression, to keep the relative tax burden per worker constant, has a wage moderating and a positive effect on employment and negative effect on outsourcing.
Keywords: H22; J41; J51; 330; Nash wage bargaining; outsourcing; labor tax reform; Lohnverhandlungstheorie; Lohnbildung; Outsourcing; Kosten; Lohnsteuer; Steuerprogression; Beschäftigungseffekt; Theorie